Adsorption properties of Ni cluster modified TiO2 (1 0 1) towards SF6 decomposition gases. (28th October 2022) - Gui, Yingang; Yang, Shun; Ji, Chang; Chen, Xianping
Abstract: Online detection of insulation defects the decomposition products of SF6 plays a key role in ensuring the safe operation of the gas‐insulated switchgear (GIS) equipment. The pristine TiO2 (1 0 1) modified by Ni cluster (1–3 Ni atoms) is used as a new gas‐sensing material to study its gas‐sensing characteristics to the characteristic decomposition products of SF6 : SO2, SOF2, and SO2 F2 . Through density functional theory (DFT) calculation, we found that the modification of Ni clusters significantly improved the conductivity of pristine TiO2 (1 0 1) and the gas sensitivity of SF6 decomposition products. More importantly, the change of conductivity after gas adsorption lays a theoretical foundation for identifying the type and concentration of SF6 characteristic decomposition products and further judging the type of defects in GIS.